The Effect of Millennial Transformational Leadership on IT Capability, Organizational Agility and Organizational Performance in the Pandemic Era: an Empirical Evidence of Fishery Startups in Indonesia - Albert Surya Wanasida; Innocentius Bernarto; Niko Sudibjo (ADI Publisher, 2020)
This study aims to understand: Does millennial transformational leadership influence organizational performance, organizational agility and IT capability? Does IT capability influence organizational agility? Does organizational agility influence organizational performance? The population of this study included selected fishery startups in Indonesia based on the data released by the Ministry of Marine Affairs and Fisheries of Republic of Indonesia and Digital Fishery Network. This study used the statistical method of PLS-SEM to analyze the data. The findings show that there is a positive relationship between millennial transformational leadership and organizational agility, millennial transformational leadership and IT capability, IT capability and organizational agility, and organizational agility and organizational performance. Future researches are suggested to examine the effects of several mediating variables in the proposed model.